Electrical selection for planktonic sludge microbial community function and assembly. (1st November 2021) - Wang, Aijie; Shi, Ke; Ning, Daliang; Cheng, Haoyi; Wang, Hongcheng; Liu, Wenzong; Gao, Shuhong; Li, Zhiling; Han, Jinglong; Liang, Bin; Zhou, Jizhong
Highlights: The electroselected planktonic sludge with higher azo dye transformation efficiency. The sludge community structure and function was changed upon electrostimulation. More interactions of fermenters and decolorizers evolved upon electrostimulation. Azo/nitroreductase and quinone synthesis genes enriched in decolorizers. Deterministic microbial community assembly dominated upon electrostimulation. Abstract: Electrostimulated hydrolysis acidification (eHA) has been used as an efficient biological pre-treatment of refractory industrial wastewater. However, the effects of electrostimulation on the function and assembly of planktonic anaerobic sludge microbial communities are poorly understood. Using 16S rRNA gene and metagenomic sequencing, we investigated planktonic sludge microbial community structure, composition, function, assembly, and microbial interactions in response to electrostimulation. Compared with a conventional hydrolysis acidification (HA) reactor, the planktonic sludge microbial communities selected by electrostimulation promoted biotransformation of the azo dye Alizarin Yellow R. The taxonomic and functional structure and composition were significantly shifted upon electrostimulation with azo dyes degraders (e.g. Acinetobacter and Dechloromonas ) and electroactive bacteria (e.g. Pseudomonas ) being enriched. More microbial interactions between fermenters and decolorizing and electroactive bacteria, as well as fewer interactions between different fermenters evolved in the eHA microbial communities. Moreover, the decolorizing bacteria were linked to the higher abundance of genes encoding for azo- and nitro-reductases and redox mediator (e.g. ubiquinone) biosynthesis involved in the transformation of azo dye. Microbial community assembly was more driven by deterministic processes upon electrostimulation. This study offers new insights into the effects of electrostimulation on planktonic sludge microbial community function and assembly, and provides a promising strategy for the manipulation of anaerobic sludge microbiomes in HA engineering systems. Graphical abstracts: Image, graphical abstract